'A new power structure will be built from the grassroots': The challenge of radical democracy in Allende's Chile. (1st June 2021) - Schlotterbeck, Marian
Abstract : Chilean history in the twentieth century poses a number of unresolved questions about the limits of liberal capitalist democracy to effectively include the interests of non-elite sectors. The origins of the contemporary crisis for Chile's political elites – as well as of neoliberalism more broadly – can be found in the chasm between political parties and their social bases. The parallels faced by Chilean activists and protestors in 2019 invite a closer look at the possibilities for and restraints on popular sector participation during Chile's experiment with democratic socialism. As an act of radical democracy, the 1972 People's Assembly in Concepción represented a vital attempt to create new mechanisms for citizen participation within an unfolding revolutionary process. Today, as Chileans grapple with how to construct an alternative to neoliberal democracy, past historical experiments in radical democracy and building grassroots movements can offer important lessons for the present.